Physical activity habits and their relationship with sociodemographic factors in Chilean adolescents - Fuentealba-Urra, Sergio; Rubio, Andrés; Flores-Rivera, Carol; González-Carrasco, Mónica; Oyanedel, Juan Carlos; Castillo-Quezada, Humberto; Céspedes-Carreño, Cristian; Pacheco-Carrillo, Jaime (Frontiers in Psychology, 2022)
Physical activity plays an important role in the well-being and development of adolescents. Physical activity habits expressed in terms of frequency and duration are consistently associated with sociodemographic factors such as age, gender and socioeconomic status. However, there is less evidence on the relationship between the type and context of physical activity practice in adolescents. The aim of this article is to analyze physical activity habits and their relationship with sociodemographic factors in Chilean adolescents. The cross-sectional study considered a sample of 7,263 adolescents aged 10 to 20 years, students from public and private schools in all regions of Chile. Physical activity habits were examined by means of a self-report questionnaire. The age groups were established based on UNICEF considerations for adolescents. Socioeconomic level was established based on the school vulnerability index (SVI) of the school attended by each adolescent. It was possible to observe that a significant part of the physical activity habits of adolescents are below the international recommendations. A statistically significant association can also be found between the sociodemographic factors studied and the physical activity habits reported by the young people. The multivariate regression analysis established that the risk of presenting unhealthy physical activity habits was 2.8 times higher in females vs. males, 2.4 times higher in the older age groups (14-16 and 17-21 years old) vs. the 10-13 years age group, and 11% more likely in the medium and high vulnerability groups vs. the low socioeconomic vulnerability group. These findings highlight the importance of considering these factors as a whole when designing programs or public policies that promote the development of healthy physical activity habits in adolescents.